2019
DOI: 10.1371/journal.pone.0222019
|View full text |Cite
|
Sign up to set email alerts
|

The impact of door-to-electrocardiogram time on door-to-balloon time after achieving the guideline-recommended target rate

Abstract: BackgroundLittle is known about the components and contributing factors of door-to-balloon time after implementation of Door-to-Balloon Alliance quality-improving (QI) strategies, including the impact of door-to-ECG time on door-to-balloon time.ObjectiveWe investigated whether modification of emergency department (ED) triage processes could improve door-to-ECG and door-to-balloon times after implementation of QI strategies.MethodsThis was a retrospective before-and-after study of a prospectively collected data… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
23
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 17 publications
(24 citation statements)
references
References 28 publications
0
23
0
1
Order By: Relevance
“…Although assigning a technician and ECG equipment to the conduction of triage ECG has been shown effective for reducing DTE time [8,17,[23][24][25], indiscriminate ECG screening without a patient interview by an experienced emergency physician has raised the concern of increasing workload among nursing staff as well as the possibility of low costeffectiveness [16]. Indeed, a previous study has reported a 30% increase in ECG workload after implementation of a triage ECG program [10]. By combining the strategies of cardiac triage and triage ECG, Coyne et al have shown a reduction of DTE time by 39% (i.e., from 23 to 14 minutes) and DTB by 12% (from 85 to 75 minutes).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Although assigning a technician and ECG equipment to the conduction of triage ECG has been shown effective for reducing DTE time [8,17,[23][24][25], indiscriminate ECG screening without a patient interview by an experienced emergency physician has raised the concern of increasing workload among nursing staff as well as the possibility of low costeffectiveness [16]. Indeed, a previous study has reported a 30% increase in ECG workload after implementation of a triage ECG program [10]. By combining the strategies of cardiac triage and triage ECG, Coyne et al have shown a reduction of DTE time by 39% (i.e., from 23 to 14 minutes) and DTB by 12% (from 85 to 75 minutes).…”
Section: Discussionmentioning
confidence: 99%
“…As a DTE time over 10 minutes is an indicator of unacceptable emergency medical practice [1], we investigated the effectiveness of our interventions for reducing the DTE time by selecting the predictors previously reported to be related to DTE > 10 minutes, including the female gender [9], STEMI without chest pain [10,15], relatively non-severe initial presentations (i.e., Triage Category III, IV, V) [22], and walkin patients [8], for analysis. Among them, DTE time of STEMI patients assigned into a low (i.e., less severe) triage category was signi cantly improved after intervention.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…www.nature.com/scientificreports/ Effectiveness of interventions for improving DTE times. Our literature search identified four reported contributors to DTE delays, including STEMI without chest pain, underestimated disease severity (i.e., initially low triage levels of III-V), walk-in patient, and female gender [8][9][10]15,22 . Therefore, the four factors were used for evaluating the effectiveness of the program for improving DTE times in STEMI patients.…”
Section: Methodsmentioning
confidence: 99%
“…Rapid performance of electrocardiography (ECG) for STEMI identification is crucial to achieving coronary artery reperfusion. Some studies have shown that improving DTE time can shorten DTB time 8 10 . Although a previous large-scale multicenter study has demonstrated no significant reduction in 30-day in-hospital mortality rate for STEMI patients achieving the target time of DTB within 90 min, improving DTE and DTB times should still be persistently emphasized owing to the potential benefits of long-term reduction in mortality, improvement in left ventricular function, and decreasing the number of admissions for heart failure 11 .…”
Section: Introductionmentioning
confidence: 99%